Realizing Restorative Justice through Mediation - Attas, Nasrah Hasmiati; Hasmiati Attas, Nasrah; Nasir, Citra; Eka Saputra, Tri; Gilang, Abbas (Cendekiawan Indonesia Timur, 2022)
Disputes can arise at any time in human life, unwanted and unexpected by anyone. Ideally, law enforcement can realize the objectives of the law, namely justice, benefit, and legal certainty. The settlement is often done through legal channels, and the most recognized by the public is dispute resolution through the courts, which usually takes a long time and is expensive. Mediation can be used as an alternative in dispute resolution because it can be done either inside or outside the court so that it can realize restorative justice. The purpose of this training is for each community to understand alternative ways to resolve various disputes through mediation, which is the right way to resolve legal issues without going to court. The outputs of this activity are 1) Knowing the role of the mediator and 2) Understanding the mediation process. 3) Improve skills to become a competent mediator.